2008
DOI: 10.1194/jlr.m800048-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the role of a retroendocytosis pathway in ABCA1-mediated cholesterol efflux from macrophages

Abstract: The ATP binding cassette transporter A-1 (ABCA1) is critical for apolipoprotein-mediated cholesterol efflux, an important mechanism employed by macrophages to avoid becoming lipid-laden foam cells, the hallmark of early atherosclerotic lesions. It has been proposed that lipid-free apolipoprotein A-I (apoA-I) enters the cell and is resecreted as a lipidated particle via a retroendocytosis pathway during ABCA1-mediated cholesterol efflux from macrophages. To determine the functional importance of such a pathway,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 38 publications
8
48
1
1
Order By: Relevance
“…The fact that apoA-I lipidation and HDL release was fully recovered after WGA removal from the plasma membrane supports this notion. Our conclusion is also consistent with recent reports that HDL is primarily generated on the plasma membrane (44,45).…”
Section: A937vsupporting
confidence: 83%
“…The fact that apoA-I lipidation and HDL release was fully recovered after WGA removal from the plasma membrane supports this notion. Our conclusion is also consistent with recent reports that HDL is primarily generated on the plasma membrane (44,45).…”
Section: A937vsupporting
confidence: 83%
“…Cell surface expression of ABCA1 permits the transporter to transfer cholesterol and phospholipid to apoA-I, which is present in the extracellular environment (23,24). β1-Syntrophin binds ABCA1 through the PDZ motif in the ABCA1 C-terminal domain, and the positive effect that β 1-syntrophin has on the trafficking of ABCA1 likely is mediated by the ability of β 1-syntrophin to recruit utrophin, a cytoskeletal binding protein, to the ABCA1 complex (12,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting that only these two tissues quantitatively produce apoA-I (56). There is also mounting evidence that assembly of most HDL particles occurs at the cell surface (45,(58)(59)(60)(61)(62)(63)(64) or in a recycling endosomal compartment by ABCA1 (65)(66)(67)(68)(69)(70) and not in the secretory pathway of the endoplasmic reticulum and Golgi apparatus (71). Because we have shown that poorly lipidated apoA-I (i.e., pre-b1 HDL) is rapidly catabolized by the kidney, whereas lipid-free apoA-I rapidly and quantitatively transfers to plasma HDLs (17,51), newly synthesized apoA-I from hepatocytes or intestinal epithelial cells has several metabolic fates.…”
Section: Discussionmentioning
confidence: 99%